Limit of Function Understanding by Student of National Mathematics Olimpiad ON MIPA in University - Tonra, Wilda Syam; Suryadi, Didi; Kusnandi, Kusnandi; Mulyaning. A, Endang Cahya (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
Limits of function is one of sub-topic of Calculus that is complex and difficult to understand. Several studies, both examining misconception and understanding related to function limits, aim to improve teaching and learning. This research is single Subject Research with a single subject, namely by Student of National Mathematics Olimpiad ON MIPA in University. Data was collected through a test instrument consisting of 7 questions on understanding function limits and interviews were conducted to confirm the subject's answers. Data analysis is qualitative. The research results show that 1) Subject can determine the limit value of the function. However, the subject still has a partial understanding. 2) Subject does not understand the meaning of function limits. The subject believes that if there are 2 functions with the same function limit value, then both functions will be the same. 3) Subject can determine the value of the left limit and the right limit from the graph of the given function. 4) Subject cannot formally prove (epsilon-delta) the limit value of the function, the subject does not yet understand what information is given, what information will be sought. The subject is also not able to determine the delta limit in proof problems that have factors 5) Subject can determine the limit value at infinity 6) Subject can determine the value of infinite limit 7) Subject can investigate whether a function is continuous or not continuous. The conclusion of the research is that from 7 understandings of function limits, the subject has 4 perfect understandings regarding left and right limits, limits at infinity and infinity and function continuity. However, the subject was not yet able to prove the limit (epsilon-delta).